Global weak solutions of the Navier?Stokes?Fokker?Planck system - Egorov, S. M.; Khruslov, E. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We consider a coupled system of the Navier- Stokes and Fokker- Planck equations that describes the motion of a polydisperse suspension of solid particles in a viscous incompressible liquid. We prove the existence theorem and study some properties of global weak solutions of the initial boundary-value problem for this system.